Asas Kebebasan Berkontrak dalam Perjanjian Surogasi di Indonesia dari Perspektif Hukum Perdata dan Etika - Martiana, Annisa Ayu (Faculty of Law Hang Tuah University, 2024)
Every couple hopes to have children to continue their lineage, but some face difficulties. Modern medical technology, such as In Vitro Fertilization (IVF), offers solutions through surrogacy or womb rental, which involves a contract between the couple and a surrogate. In Indonesia, this practice lacks a clear legal foundation, creating ethical and legal dilemmas. This study aims to explore the application of the principle of freedom of contract in surrogacy agreements from a civil law and ethical perspective. Regarding to the Article 1320 of the Indonesian Civil Code, the study's findings indicate that surrogacy agreements do not meet the objective criteria for a valid contract because the object of the contract, the womb, cannot be considered a legal object or commodity under civil law. Furthermore, the commercialization of the womb conflicts with prevailing moral and ethical values, rendering the agreement null and void by law.